Effectiveness of Choice Theory Intervention on Emotional Divorce and Emotional Self-Differentiation in Women with Marital Conflict Referring to Psychological Centers of Isfahan: A Quasi-Experimental Study - Fatemi, Mahboubeh Sadat; Kazemian Moghaddam, Kobra; Gholamzadeh Jofreh, Maryam (Advances in Nursing & Midwifery, 2024)
Introduction: Marital conflict can lead to emotional detachment (emotional divorce) and hinder a woman's ability to manage her emotions effectively (emotional self-differentiation). Choice theory, with its emphasis on personal responsibility and need fulfillment, offers a potential framework for improving these outcomes. This study investigates the effectiveness of choice theory intervention on emotional divorce and emotional self-differentiation in women with marital conflict referring to the psychological centers of Isfahan. Methods: The current study employed a quasi-experimental design with a pre-test-post-test structure and a control group. The target population encompassed all women experiencing marital conflict who sought services at Isfahan's psychological centers during the year 2023. A convenience sampling method was utilized to recruit a sample of 30 participants (15 per group) who met the study's inclusion criteria. Random assignment procedures were employed to allocate participants to either the experimental or control group. Both groups completed the Emotional Divorce Inventory and the Differentiation of Self Inventory at both the pre-test and post-test stages. The experimental group then received the choice theory intervention, delivered in eight 90-minute sessions. Data analysis was conducted using analysis of covariance (ANCOVA). Results: The experimental group demonstrated a significant decrease in emotional divorce scores from 56.13±2.20 pre-intervention to 34.87±3.98 post-intervention. In contrast, the control group showed no significant change in emotional divorce scores. The experimental group also exhibited a significant increase in emotional self-differentiation scores from 118.40±8.11 pre-intervention to 183.80±12.39. The control group experienced a slight increase in emotional self-differentiation scores, but the change was not statistically significant. These findings suggest that the choice theory intervention is effective in reducing emotional divorce and enhancing emotional self-differentiation among women experiencing marital conflict (P<0.001). Conclusions: These results suggest that choice theory intervention has the potential to be a valuable tool for improving emotional connection and emotional regulation in women facing marital discord.